SOME WAYS OF IMPROVING CHILDREN’S SPEAKING SKILL - Yuldsheva S.F; Rahimov Asadbek Anvarjon o`g`l i (Journal of new century innovations, 2022)
Annotation: The article deals with the problems of improving children's speaking skill. Speaking skill is regarded as a very complex process, the majority of foreign language students encounter various problems with classroom speaking activities.